Dynamic Protection of Innovations through Patents and Trade Secrets - Paul Belleflamme; Paul Bloch (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper analyzes the optimal protection strategy for an innovator of a complex innovation who faces the risk of imitation by a competitor. We suppose that the innovation can be continuously fragmented into sub-innovations. We characterize the optimal mix of patent and trade secrets when the innovator faces a strict novelty requirement and can only patent a fraction of the innovation once. We also study the optimal dynamic patenting policy in a soft novelty regime, when the innovator can successively patent different fragments of the process. We compare a regime with prior user rights, when the innovator can use the secret part of the process, even when it is patented by an imitator with a regime without prior user rights.
Keywords: O31; O34; 330; patents; trade secrets; dynamic protection of innovation; intellectual property rights